2002
DOI: 10.1002/mrm.10304
|View full text |Cite
|
Sign up to set email alerts
|

Brain metabolite composition during early human brain development as measured by quantitative in vivo 1H magnetic resonance spectroscopy

Abstract: Biochemical maturation of the brain can be studied noninvasively by 1 H magnetic resonance spectroscopy (MRS) in human infants. Detailed time courses of cerebral tissue contents are known for the most abundant metabolites only, and whether or not premature birth affects biochemical maturation of the brain is disputed. Hence, the last trimester of gestation was observed in infants born prematurely, and their cerebral metabolite contents at birth and at expected term were compared with those of fullterm infants.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
188
10
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(222 citation statements)
references
References 35 publications
16
188
10
3
Order By: Relevance
“…23 This was set in the LCModel parameter "WCONC" rather than 35,880 mmol/L used as the default value for white matter, which underestimates the absolute metabolite concentrations. 24,25 Based on the LCModel output, MR spectra with line width at full width at half maximum of Ͼ0.1 ppm (approximately 6 Hz) and/or SNR of Ͻ3 were excluded. Metabolite concentrations with a confidence level of the Cramer-Rao lower bounds 26 of Ͼ20% were also excluded from the subsequent analysis.…”
Section: Mr Spectroscopy Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…23 This was set in the LCModel parameter "WCONC" rather than 35,880 mmol/L used as the default value for white matter, which underestimates the absolute metabolite concentrations. 24,25 Based on the LCModel output, MR spectra with line width at full width at half maximum of Ͼ0.1 ppm (approximately 6 Hz) and/or SNR of Ͻ3 were excluded. Metabolite concentrations with a confidence level of the Cramer-Rao lower bounds 26 of Ͼ20% were also excluded from the subsequent analysis.…”
Section: Mr Spectroscopy Processingmentioning
confidence: 99%
“…7 This tCho peak, however, only reflects a small part of the tissue level of Cho-containing compounds. More than 90% of the latter is phosphatidylcholine, a major constituent of the phospholipids that form myelin, 42,43 which cannot be detected by 1 H-MRS. 44 The tCho exhibits a higher concentration during early life than in adulthood, which indicates that Chocontaining compounds are turned over more rapidly during early human development 24,45 and decrease over the first 5 years of life. 46,47 We also showed that tCho:tCr decreases with increasing GA, whereas tCho remains relatively stable until the beginning of myelination toward the end of the third trimester of pregnancy and early postnatal period.…”
mentioning
confidence: 99%
“…There are significant age-dependent changes of metabolites particularly during the first months of life. [23][24][25] Controls were consequently subdivided into 2 groups, of which the first group age-matched with the patients included only subjects older than 6 months, an age by which the most dramatic changes of biochemical brain maturation have already occurred. 23 The second group included neonates and infants younger than 6 months.…”
Section: Detection Of "Apparent" Citrate In Controlsmentioning
confidence: 99%
“…5 Brain 1 H MRS identifies several metabolites of biological importance, including lactate. 6 It has been demonstrated that elevated levels of lactate detected by 1 H MRS in the brain of asphyxiated neonates are predictive of neurodevelopmental delay. 7,8 Plasma lactic acid concentration is indeed higher in IUGR fetuses with altered umbilical arterial Doppler velocimetry and abnormal fetal heart rate 9,10 ; however, little is known about intrauterine changes in cerebral metabolism in IUGR fetuses.…”
mentioning
confidence: 99%